2018
DOI: 10.1080/2162402x.2018.1480300
|View full text |Cite
|
Sign up to set email alerts
|

Proteinase-nicked IgGs: an unanticipated target for tumor immunotherapy

Abstract: The host immune system adopts multiple mechanisms involving antibodies to confront cancer cells. Accordingly, anti-tumor mAbs have become mainstays in cancer treatment. However, neither host immunity nor mAb therapies appear capable of controlling tumor growth in all cases. Structural instability of IgG was overlooked as a factor contributing to immunosuppression in the tumor microenvironment. Recently, physiological proteinases were identified that disable IgG immune effector functions. Evidence shows that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Possible hypotheses for the clearance-associated efficacy are consumption of therapeutic proteins or proteolytic cleavage of the hinge region of Fc fusion proteins by tumors. [16][17][18][19][20] Thus, luspatercept CL/F may be a good estimate of catabolic activity, reflecting severity of the disease or anemia that impact the response to treatment. Similar hypotheses have been used to explain the association of slower clearance of several antitumor monoclonal antibodies with better antitumor efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Possible hypotheses for the clearance-associated efficacy are consumption of therapeutic proteins or proteolytic cleavage of the hinge region of Fc fusion proteins by tumors. [16][17][18][19][20] Thus, luspatercept CL/F may be a good estimate of catabolic activity, reflecting severity of the disease or anemia that impact the response to treatment. Similar hypotheses have been used to explain the association of slower clearance of several antitumor monoclonal antibodies with better antitumor efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…It is currently up to speculation if these enzymes could even partly dissociate or cleave tumor-specific IgG1 antibodies, rendering them available for IgG4 Fc–Fc interaction [ 67 ]. In a recent breast cancer study, the presence of cleaved IgG antibodies was found in the TME in tumor tissue extracts [ 68 ].…”
Section: Igg4 As a Key To Immune Tolerance In Cancermentioning
confidence: 99%
“…4 Furthermore, mAbs have been significantly improved as a form of cancer treatment over the years, with most recent developments focusing on making current mAbs proteinase-resistant and creating new antihinge antibodies, such as c7E3 IgG, capable of counteracting the IgGinactivating microenvironments of tumors. 5 An emerging and alternative class of biomaterials for synthetic immunology is engineered cells expressing novel natural or synthetic genes that guide and induce an immune response in patients. Engineered mammalian cells have several desirable properties as a therapeutic platform including the ability to support large networks of transgenes, 6 the potential to be drawn from the patient themselves, 7 and the inherent ability to perform useful functions such as migration, secretion, membrane fusion, and target-cell lysis.…”
mentioning
confidence: 99%
“…Patients treated with Ipilimumab were found to have a significantly increased overall survival rate from 25.3% to 45.6%, when compared to previously popular gp100 antigen treatment . Furthermore, mAbs have been significantly improved as a form of cancer treatment over the years, with most recent developments focusing on making current mAbs proteinase-resistant and creating new antihinge antibodies, such as c7E3 IgG, capable of counteracting the IgG-inactivating microenvironments of tumors …”
mentioning
confidence: 99%